Synergistic ultrasonic-microwave assisted extraction (UMAE) for enhanced fat extraction from nutmeg seeds - Afifah, Meita; Teguh, Dedi; Shintawati; Ramandani, Adityas Agung (Jurnal Rekayasa Proses, 2025)
Nutmeg seeds contain essential oils and fats, are widely used in the cosmetic and pharmaceutical industries. This research aims to determine the yield, physicochemical characteristics and fat composition of nutmeg seeds extracted from Ultrasonic-Microwave Extraction (UMAE). The research used a factorial completely randomized design (CRD) method with the independent variables, length of extraction time (45, 90, 135 minutes) and microwave power (300 and 450 watts). The dependent variables in this research are yield, melting point, specific gravity, acid number and saponification number. The results showed that the highest fat yield of nutmeg was 30.48% at 300 Watts and 135 minutes. The physicochemical characteristic of nutmeg fat was yellow with specific gravity, melting point, acid number and saponification number were 0.96, 52.4 °C, 16.69 mg KOH/g fat and 254.96 mg KOH/gram fat. GCMS results show that the fat composition is trichloromethyl, isopropyl phosphoranidothioic acid and lauric acid triglyceride which have potential as cosmetic raw materials.